Community Empowerment through Family Medicinal Plant (TOGA) Cultivation and Product Innovation to Improve Health and Local Economy - Anggraini, Artanti; Aliya, Septia Mita; Zafirah, Maia Alma; Pinkan, Cinta Revallina; Rahayu, Widia; Sudrajat, Cecep; Triastinurmiatiningsih (Jurnal Pengabdian Masyarakat Inovatif, 2025)
Parakan Village, Ciomas District, Bogor Regency, has considerable potential for the development of Family Medicinal Plants (TOGA) supported by household yards and unused land; however, community capacity in cultivation and product processing remains limited. This community empowerment program aimed to improve health literacy and strengthen the local economy through participatory training and mentoring in TOGA cultivation and value-added product innovation using a service-learning approach. The program involved 30 community members and focused on ginger, turmeric, galangal, cat’s whiskers, lemongrass, and betel. Program effectiveness was evaluated through pre–post-test, observations, and interviews. The results indicated a 53% increase in participants’ knowledge of TOGA cultivation and a 41% improvement in processing skills. In addition, three TOGA-based innovative products were successfully developed, namely JASEYO herbal yogurt, LUSHJAM infused water, and SEJIWA herbal drink, and were supported by digital-based commercialization through the Digital Herbal Village platform. Overall, the integration of TOGA cultivation, product innovation, and digital marketing contributes to improved community health capacity and creates sustainable local economic opportunities.